Methodological Recommendations of the Ministry of Health of Ukraine on the Organization of Medical Care for Victims of Hostilities - Siromakha, Sergii O.; Kulbachnyi, Oleksandr S. (Ukrainian Journal of Cardiovascular Surgery, 2022)
During the war, it is important to properly organize medical care on various stages. The Ministry of Health of Ukraine has adopted several guidelines in order to standardize medical care provided by physicians in various fields. In this material, we schematically present the basic algorithms of action of medical specialist, both at the pre-hospital and hospital level, in cases of gunshot wounds, massive bleeding and burns. In addition, a special place is given to stabilizing the patient’s psychological state and prevention of post-traumatic stress disorder.